France's war in Mali : lessons for an expeditionary army - Shurkin, Michael Robert (2014)
In 2013, just as U.S. Army Chief of Staff General Raymond Odierno was articulating a particular vision for expeditionary operations, the French Army was fielding a force in Mali that in many ways provided a real-world example of the kind of operations Odierno envisioned. France fielded a relatively small force put together using small, scalable combined arms taskorganized units as basic building blocks and conducted a campaign that emphasized speed and maneuver over force protection. The French force, moreover, is for all intents and purposes regionally aligned, and it demonstrated the benefits that could accrue through its apparently effective operations among and with local and regional actors. The French also have a force structure well suited to expeditionary operations in austere environments, as well as an expeditionary institutional culture.